2002
DOI: 10.1103/physrevb.66.052420
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and mechanical stability ofα-iron

Abstract: Ab initio electronic structure calculations employing the fixed-spin moment procedure and the generalized gradient correction are used to explore the mechanical stability of ␣-iron and related magnetic materials, including body-centered-cubic cobalt and ziconium. The mechanical stability is found to depend sensitively on the magnetization. At relatively low values of the magnetization, specific vibrational and elastic instabilities are identified and are interpreted in terms of the behavior of the electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 19 publications
5
12
1
Order By: Relevance
“…[4]. The magnetic moment M of bcc Fe at zero pressure is 2.2 µ B (µ B is Bohr magnetic moment) which is accordant with the experimental and other calculated values [15] . is located at 0 eV and indicated by dash dot line, as shown in Fig.…”
Section: Electronic Structuresupporting
confidence: 82%
“…[4]. The magnetic moment M of bcc Fe at zero pressure is 2.2 µ B (µ B is Bohr magnetic moment) which is accordant with the experimental and other calculated values [15] . is located at 0 eV and indicated by dash dot line, as shown in Fig.…”
Section: Electronic Structuresupporting
confidence: 82%
“…This approximation has been successfully applied in other DFT studies of paramagnetic systems such as fcc and bcc iron. 24,28,29 In addition, and to get a better understanding of the electronic structure at the surface, we simulated scanning tunneling microscopy (STM) of the surfaces considered in this work. The constant-current mode STM images and line scans for vivianite surfaces with both positive and negative bias voltages were computed.…”
Section: ■ Computational Details and Methodsmentioning
confidence: 99%
“…Instead we turn to a combination of molecular dynamics and electronic structure calculations. Souvatzis et al (2008Souvatzis et al ( , 2009) developed the so-called selfconsistent ab initio lattice dynamical (SCAILD) calculations, which is a quantum-mechanical realization of the selfconsistent phonon method (Born, 1951;Hooton, 1958;Koehler, 1968). The self-consistent phonon method was developed to treat strongly anharmonic systems where the harmonic phonon frequencies may even be unstable, such as crystals of noble gases.…”
Section: Self-consistent Phonon Calculationsmentioning
confidence: 99%
“…Ahuja et al (1993) found bcc Ti, Zr, and Hf stabilized at high pressure and T ¼ 0 K; see also Hu, Lu, and Yang (2008), and Hu et al (2010), and references therein. Hsueh et al (2002) noted that the phonon structure in bcc Zr could be stabilized if a magnetic moment was imposed.…”
Section: Scandium Yttrium and Lanthanummentioning
confidence: 99%